(untitled) (Revista Logos Ciencia & Tecnología, 2018)
In Colombia, the implementation of the educational innovation policy supported by ICT requires teachers to be competent in the use of ICT in order to provide quality education. In some cases, this becomes a trigger for technological stress, because there are teachers who see technology as a threat, this situation is the product of cognitive biases. This article makes an approximation to this phenomenon that has repercussions in the execution of public policy and in the school itself. Finally, a valid mechanism to face the problem is shown: cognitive restructuring.